Evaluation of Lorlatinib Cerebrospinal Fluid Concentrations in Relation to Target Concentrations for Anaplastic Lymphoma Kinase (ALK) Inhibition. (27th April 2022) - Sun, Steven; Pithavala, Yazdi K.; Martini, Jean‐François; Chen, Joseph
Abstract: Lorlatinib is a third‐generation, brain‐penetrant anaplastic lymphoma kinase (ALK) and c‐ros oncogene 1 (ROS1) tyrosine kinase inhibitor (TKI) with robust intracranial activity in patients with ALK‐ or ROS1‐ positive non‐small cell lung cancer (NSCLC). Data from the ongoing open‐label, single‐arm, multicenter, phase‐1/2 study of lorlatinib in patients with metastatic ALK‐ or ROS1‐ positive NSCLC were used to further investigate the potential brain penetration of lorlatinib. Patients received escalating lorlatinib doses (10–200 mg once daily or 35–100 mg twice daily) or the approved dosing (100 mg daily). Plasma was collected from all patients, and cerebrospinal fluid (CSF) was collected at baseline and during the study from 5 patients with suspected or confirmed leptomeningeal carcinomatosis or carcinomatous meningitis. For those 5 patients, lorlatinib concentrations ranged from 2.64 to 125 ng/mL in the CSF and from 12.7 to 457 ng/mL in the plasma; free plasma concentrations ranged from 4.318 to 155.385 ng/mL. The CSF/free plasma ratio was 0.77 (R 2  = 0.96 and P  < .001). Using a post‐hoc population pharmacokinetic model, the average steady‐state unbound plasma concentration of lorlatinib was derived and the CSF concentration was estimated for all patients. Known minimum efficacy concentrations (Ceff ) for wild‐type and mutated (L1196M and G1202R) ALK were used to derive central nervous system (CNS) Ceff . Estimated CNS concentrations exceeded the derived CNS Ceff values in all patients for wild‐type ALK and the ALK L1196M mutation, and in 35.8% of patients for the ALK G1202R mutation. Projected lorlatinib CNS concentrations were consistent with the high intracranial response rates reported in clinical trials and provide further evidence of the potent CNS penetration of lorlatinib.